The Circular Economy, Bioeconomy, and Green Investments: A Systematic Review of the Literature - Berto, Pietro Jacomini; Ferraz, Diogo; Rebelatto, Daisy Aparecida do Nascimento (Revista Gestão da Produção Operações e Sistemas, 2022)
Purpose – This study aims to evaluate the theoretical concept of the Bioeconomy and the Circular Economy in association with studies about green finance. Theoretical framework – Several studies pointed out that sustainable investments must replace production processes. This literature provides a favorable environment for new studies on the Circular Economy and Bioeconomy. However, the literature lacks definitions and differentiation between both concepts. Design/methodology/approach – A Systematic Literature Review (SLR) was adequate to systematize the information from 345 articles, 231 relating to the Circular Economy, and 114 articles relating to the Bioeconomy. In addition, the contents of the 24 articles with the highest number of citations was reviewed. Findings – Our analysis revealed that the concepts of the Circular Economy and Bioeconomy could be similar or different. The concepts are similar due to the concern with sustainable economic development. However, the Circular Economy uses concepts that are related to the differentiation of the paradigm from a linear productive system to that of a loop. The Bioeconomy is more concerned with the use of biological resources and biotechnology. A geographic distribution of the studies can also identify the differences as well as the number of publications, citations, and methods used. However, both approaches equally show a scarcity of databases. Originality/value – Our study reveals that the Bioeconomy concept is hardly used in countries with high biodiversity, for example, countries that make up the Amazon region. On the other hand, there was a greater synergy between the Circular Economy approach and production processes in different economic sectors in developing countries. Keywords: Circular Economy; Bioeconomy; Green Finance; Systematic Literature Review (SLR).